Influence analysis of capital shopping and local own-source revenue on non-food shopping - Marce Sherly Kase; Egidius I Laka (International Journal of Financial, Accounting, and Management, 2019)
Purpose: The main purpose of this study was to examine the effect of Capital Expenditure and Local Own-Source Revenue (PAD) on Non-food Expenditure of the population; in North Central Timor Regency. Research methodology: This research was a quantitative study that used time series data and located in North Central Timor Regency. Descriptive statistic and Multiple linear regressions were used as statistic tools. SPSS Version 23 was used for data analysis. Results: The results of this study indicate that PAD has a significant effect on non-food shopping of the population in North Central Timor Regency. Limitations: This study it only generalized the problem that occurred in North Central Timor Regency Contribution: These findings could be very significant information to North Central Timor Regency. Keywords: Capital Expenditure, Local Own-Revenue, Non-Food Expenditure